The influence of the resistance layer dimension and interface doping on the electrical properties of aGNR/NiO/aGNR-structured resistive random access memory. (13th September 2019) - Ding, Cheng; Dai, Yuehua; Ma, Chengzhi; Lu, Wenjuan; Wang, Feifei; Zeng, Yejuan
Abstract: A first-principles method based on density functional theory is used to study the effects of the resistance layer dimension and interface doping on the electrical properties of aGNR/NiO/aGNR-structured resistive random access memory. First, calculations of the interface adhesion energy and Mulliken mean populations show that the aGNR/unilaminar NiO interface has good interface stability. Second, the current–voltage characteristics and the micro formation process of conducting filaments of graphene/NiO/graphene resistive random access memory with resistance layers of different widths are studied. The comprehensive performance of the device is fully exploited, and its storage window can satisfy the requirement of data storage when the width of the resistance layer is 17.6 Å. Finally, an increase in the concentration of excess oxygen causes an increase in power consumption and a decline in the current drive capacity, while the stability of the device is improved; moreover, the size of the storage window decreases but still meets the requirement of data storage. In summary, the storage performance is effectively improved by excess oxygen concentration of 3.82%. These results may provide a theoretical basis for rational design and device optimization regarding the resistance layer dimension and excess oxygen.